Effect of low-temperature annealing on defect causing copper-related light-induced degradation in p-type silicon. (September 2017) - Vahlman, Henri; Haarahiltunen, Antti; Kwapil, Wolfram; Schön, Jonas; Yli-Koski, Marko; Inglese, Alessandro; Modanese, Chiara; Savin, Hele
Abstract: Copper is a common impurity in photovoltaic silicon. While reported to precipitate instantly in n-type Si, copper causes light-induced degradation (Cu-LID) in p-type Si. Recently, partial recovery of Cu-LID was observed after only few minutes of dark annealing at 200 °C. In this contribution, we investigate the effects of the dark anneal on Cu-LID-limited minority carrier lifetime both experimentally and by simulations. Surprisingly, after initial recovery, the dark anneal results in further degradation corresponding to a many-fold increase in recombination activity compared to the degraded state after illumination. This anneal-induced degradation can potentially cause additional losses in accidentally Cu-contaminated devices when exposed to elevated temperatures, for example during recovery and regeneration treatments of solar cells. Transient ion drift measurements confirmed that the anneal-induced degradation cannot be attributed to residual interstitial Cu after illumination. After hundreds of hours of annealing, the samples showed another recovery. To analyze these experimental results, a comparison to simulations is performed at the end of the paper.